2022
DOI: 10.1097/scs.0000000000009095
|View full text |Cite
|
Sign up to set email alerts
|

The Craniofacial Collaboration UK: Developmental Outcomes in 5-Year-Old Children With Metopic Synostosis

Abstract: The Craniofacial Collaboration (CC-UK) was setup in 2015 as a joint initiative between the Psychology teams attached to the 4 highly specialized craniofacial centers in the United Kingdom. The CC-UK aims to address key limitations in the existing craniofacial literature by applying strict exclusion criteria and collating clinical data on a homogenous sample of children. This article reports the fourth wave of data collection from the CC-UK, with the analysis of developmental and behavioral outcomes for childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
3
3
0
Order By: Relevance
“…Parental reports of behavioral and emotional outcomes (SDQ) at 7 and 10 years indicated similar findings to that observed in previous CC-UK analyses of younger MS children, 25,29 with the majority falling within the average range. Difficulties with prosocial skills have been reported in previous CC-UK studies, indicated by a greater proportion of MS children in the "very high" scoring range at 3 and 5 years.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Parental reports of behavioral and emotional outcomes (SDQ) at 7 and 10 years indicated similar findings to that observed in previous CC-UK analyses of younger MS children, 25,29 with the majority falling within the average range. Difficulties with prosocial skills have been reported in previous CC-UK studies, indicated by a greater proportion of MS children in the "very high" scoring range at 3 and 5 years.…”
Section: Discussionsupporting
confidence: 80%
“…Parental reports of behavioral and emotional outcomes (SDQ) at 7 and 10 years indicated similar findings to that observed in previous CC-UK analyses of younger MS children, 25,29 with the majority falling within the average range. Difficulties with prosocial skills have been reported in previous CC-UK studies, indicated by a greater proportion of MS children in the “very high” scoring range at 3 and 5 years 25,29 . Interestingly, the prosocial domains at 7 and 10 years had the highest percentage of children falling within the “close to average” range, suggesting that these earlier concerns had possibly diminished.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations